Dehydroepiandrosterone stimulates inflammation and impairs ovarian functions of polycystic ovary syndrome. Issue 5 (23rd December 2018) - Li, Yulin; Zheng, Qin; Sun, Dan; Cui, Xinyuan; Chen, Siyi; Bulbul, Ahmmed; Liu, Shuai; Yan, Qiu
Abstract: Polycystic ovary syndrome (PCOS) is one of the most common causes of infertility in child‐bearing‐age women. It is characterized by ovulation dysfunction, polycystic ovaries, and hyperandrogenism. Inflammation is likely to be a crucial contributor to the pathogenesis of PCOS. However, the association between the inflammatory cytokines and the development of PCOS has not been reported. To explore the relationship between the inflammatory cytokines and PCOS, alterations of serum proteins in dehydroepiandrosterone (DHEA)‐induced PCOS rats were screened by protein array, and the concentration of IFN‐γ was further measured by using enzyme‐linked immunosorbent assay (ELISA). DHEA‐induced PCOS rats had a decreased level of IFN‐γ compared with the control rats, which was restored partly in flutamide (an androgen receptor antagonist)‐treated rats. Moreover, the level of IFN‐γ in serum of patients with PCOS was also lower than that in healthy women. Using the ovarian granulosa cells (KGN), we demonstrated that DHEA downregulated the expression and secretion of IFN‐γ in dose‐ and time‐dependent manners, which could be restored to some extent by treating with flutamide. Furthermore, flutamide ameliorated the inhibitory effect on cell proliferation and promotive effect on cell apoptosis by DHEA. The results also revealed that IFN‐γ promoted the proliferation but inhibited the apoptosis of KGN cells, which was suppressed by DHEA via activating the downstream PI3K/AKT signaling pathway. Taken together, these results showed that DHEA inhibited the proliferation and promoted the apoptosis of ovarian granulosa cells through downregulating the expression of IFN‐γ which could be restored by flutamide, and IFN‐γ may serve as a potential inflammatory biomarker for PCOS detection. Abstract : To explore the relationship between the inflammation cytokines and PCOS, alterations of serum proteins in dehydroepiandrosterone (DHEA)‐induced PCOS rats were screened by protein array, and the concentration of IFN‐γ was further measured by using the sandwich enzyme‐linked immunosorbent assay. DHEA‐induced PCOS rats had a decreased level of IFN‐γ compared with the control rats, which was restored partly in flutamide‐treated rats. Using the KGN cell line, we demonstrated that the DHEA downregulated the expression and secretion of IFN‐γ, which could be restored to some extent by treating with flutamide. As the results showed, DHEA inhibited the proliferation and promoted the apoptosis of ovarian granulosa cells through downregulating the expression of IFN‐γ which could be restored by flutamide, and IFN‐γ may serve as a potential inflammation biomarker for PCOS detection.